The Relationship Between Knowledge of Reproductive Health and Adolescents Attitudes to Premarital Sexuality - Selvia Nur'aini; Abi Muhlisin (Indonesian Journal of Global Health Research, 2024)
Adolescents who do not understand reproductive health will more easily develop negative views about premarital sex. This can influence casual sexual behavior. Previous studies confirmed that school educational institutions had conducted sexual education outreach with students during the introduction period to the school environment. However, school educational institutions do not know about the behavior of students outside the school area. Objective: The aim of this research was to find out whether there was a correlation between premarital sexual attitudes and reproductive health knowledge at SMK 1 Juwiring, Klaten Regency. Method: This cross sectional analytical observational study involved 90 respondents selected using stratified random sampling. In the following research, insights related to reproductive health are the independent variable and teenagers' premarital sexual attitudes are the dependent variable. Results: After data was collected through a questionnaire, the relationship was tested using the chi-square test with the result p-value=0.037 (α<0.05). Conclusions: The research results confirm that knowledge related to reproductive health and premarital sexual attitudes of adolescents are correlated with each other.